The relative influence of sea surface temperature anomalies on the benthic composition of an Indo‐Pacific and Caribbean coral reef over the last decade. Issue 9 (6th September 2022) - Johnson, Jack V.; Exton, Dan A.; Dick, Jaimie T. A.; Oakley, Joseph; Jompa, Jamaluddin; Pincheira‐Donoso, Daniel
Abstract: Rising ocean temperatures are the primary driver of coral reef declines throughout the tropics. Such declines include reductions in coral cover that facilitate the monopolization of the benthos by other taxa such as macroalgae, resulting in reduced habitat complexity and biodiversity. Long‐term monitoring projects present rare opportunities to assess how sea surface temperature anomalies (SSTAs) influence changes in the benthic composition of coral reefs across distinct locations. Here, using extensively monitored coral reef sites from Honduras (in the Caribbean Sea), and from the Wakatobi National Park located in the center of the coral triangle of Indonesia, we assess the impact of global warming on coral reef benthic compositions over the period 2012–2019. Bayesian generalized linear mixed effect models revealed increases in the sponge, and hard coral coverage through time, while rubble coverage decreased at the Indonesia location. Conversely, the effect of SSTAs did not predict any changes in benthic coverage. At the Honduras location, algae and soft coral coverage increased through time, while hard coral and rock coverage were decreasing. The effects of SSTA at the Honduras location included increased rock coverage, but reduced sponge coverage, indicating disparate responses between both systems under SSTAs. However, redundancy analyses showed intralocation site variability explained the majority of variance in benthic composition over the course of the study period. Our findings show that SSTAs have differentially influenced the benthic composition between the Honduras and the Indonesian coral reefs surveyed in this study. However, the large intralocation variance that explains the benthic composition at both locations indicates that localized processes have a predominant role in explaining benthic composition over the last decade. The sustained monitoring effort is critical for understanding how these reefs will change in their composition as global temperatures continue to rise through the Anthropocene. Abstract : Global warming continues to transform coral reef assemblages throughout the tropics, impacting biodiversity and ecosystem function. Here we identify disparate disruptions between an Indoneisan coral reef and a Honduran coral reef system under climate change over the last 10 years. " cd_value_code="text